Pengaruh Training terhadap Produktivitas Kerja Karyawan Bagian Produksi pada PT. Nestle Indonesia Kejayan Factory Pasuruan - Hastuti, Tuti (Jurnal Manajemen Akuntansi dan Bisnis, 2008)
This research was undertaken at PT. Nestle Indonesia Kejayan Factory Pasuruan. It aims to analyze the influence of training on productivity among workers in Production Division at PT. Nestle Indonesia Kejayan Factory Pasuruan. From this research, it can be known that training influences productivity among workers in Production Division at PT. Nestle research, it can be known that training influences productivity among workers in production division. This result can be seen from the correlation is 0,719 (near 1). So the relation of the two variables is strong and positive. The result of the regression can be interpreted that 1 unit of the increased training will influence the increased productivity among workers of 0,714 unit. Therefore, training will influence the increase or decrease in productivity of workers. The result of t-test show that the score of t-count > t-table, where Ho is rejected and Ha is accepted. The conclusion is that training significantly influences productivity among workers in Production division. Keywords: Training, and Productivity